Primary Children's Understanding of the Role of Historical Evidence: Comparisons Between the United States and Northern Ireland. Issue 2 (1st June 2001) - Barton, Keith
This study examines similarities and differences in the ways primary children in Northern Ireland and the United States understand the role of historical evidence. Although limited in scope, the research reported here points to critical issues in developing and expanding children's perspectives on this fundamental topic in history education, and it has implications for educators in both locations. The comparative dimension of this effort is particularly important, because studies that examine similar issues in differing national contexts can shed light on the relative importance of the variety of influences on children's understanding. Research conducted in only one setting may give the impression that identified features of children's thinking are invariant or age-related characteristics of their developments; comparative studies of students who grow up in different societies, and who have been exposed to differing curricula, can expose distinctions between the particular and the general. In Northern Ireland and the United States, children learn about history from similar kinds of sources - schools, relatives, the media, and historic sites - but the content of what they learn there is very different. A comparison of students' ideas in the two locations, then, holds promise for illustrating how these sources may interact to influence children's ideas about history.